Kesulitan Belajar Peserta Didik di SD Muhammadiyah 1 Marapalam Padang - Fani Rahma sari (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2022)
This research is motivated by students who have not been able to overcome learning difficulties at SD Muhammadiyah 1 Marapalam Padang. The purpose of this study is to describe the difficulties in learning to read, write and count.This research use desciptive qualitative approach. The instruments used in the research are observation, interviews and documentation of the cases seen. The technique used in data processing is through data reduction, data presentation and drawing conclusions. Techniques for data validity, trustworthiness, transferability, reliability. The results of this study indicate that students who have learning difficulties are: 1. Students' learning difficulties in reading occur because students do not repeat lessons at home such as reading, students experience poor vision and hearing. 2 Students' learning difficulties in writing occur because students do not practice writing at home and have blurred vision and 3. Students' learning difficulties in counting occur because of doubts in recognizing mathematical symbols and lack of practice at home. Based on the results of the study, it is recommended for parents to pay more attention to students at home so that learning difficulties experienced by students can be overcome.